A Latin American Perspective on G Protein-Coupled Receptors - Pupo, Andre S. [UNESP]; Adolfo Garcia-Sainz, J. (Amer Soc Pharmacology Experimental Therapeutics, 2016)
G protein-coupled receptors are sensors that interact with a large variety of elements, including photons, ions, and large proteins. Not surprisingly, these receptors participate in the numerous normal physiologic processes that we refer to as health and in its perturbations that constitute disease. It has been estimated that a large percentage of drugs currently used in therapeutics target these proteins, and this percentage is larger when illegal drugs are included. The state of the art in this field can be defined with the oxymoron constant change, and enormous progress has been made in recent years. A group of scientists working in Latin America were invited to contribute minireviews for this special section to present some of the work performed in this geographical region and foster further international collaboration.